The Shift to Online Psychotherapy: Adaptation and Implications for Brazilian Clinical Psychologists Amid Covid-19 - Veiga, Ana Carolina Ulhoa da; Rodrigues, Carlos Manoel Lopes; Lins, Manuela Ramos Caldas; Vidotti, Janaína de Fátima (Journal of Psychological Perspective, 2024)
The Covid-19 pandemic disrupted traditional psychotherapy practices, prompting a rapid transition to online modalities. This qualitative study investigates how Brazilian clinical psychologists adapted to online psychotherapy during and after the pandemic. Semi-structured interviews were conducted with five psychologists, each with an average professional experience of 8.9 years. Using the Iramuteq software for lexical analysis, six thematic classes were identified: uncertainties during the transition, emerging possibilities, adaptability movements, pandemic context, new professional perspectives, and academic and professional trajectories. The findings highlight significant challenges, including managing technological tools, maintaining therapeutic relationships, and addressing client concerns in virtual settings. However, the transition also revealed notable advantages, such as reduced operational costs, enhanced flexibility, and expanded access to psychological care. The analysis underscores the critical role of digital competencies, including technical, communicational, and cultural skills, in ensuring effective online therapy. Additionally, the results point to gaps in academic training and professional preparation for telepsychology, emphasizing the need for curriculum reform to include digital literacy and teletherapy-specific strategies. The study concludes that online psychotherapy represents not only a response to crisis but also a sustainable model for expanding access to mental health care. It calls for targeted professional development and ethical guidelines to support psychologists in navigating digital environments effectively. These insights contribute to understanding the evolving dynamics of psychotherapy and provide actionable recommendations for improving digital mental health services in Brazil and beyond.